Thermal, rheological, and structural behaviors of natural and modified cassava starch granules, with sodium hypochlorite solutions - Beninca, Cleoci; Colman, Tiago André Denck; Lacerda, Luiz Gustavo; Da Silva Carvalho Filho, Marco Aurélio; Demiate, Ivo Mottin; Bannach, Gilbert [UNESP]; Schnitzler, Egon (Springer Nature, 2013)
The use of chemically modified starches is widely accepted in various industries, with several applications. In this research, natural cassava starch granules were treated with standard sodium hypochlorite solution at 0.8, 2.0, and 5.0 g Cl/100 g starch. The native and modified starch samples were investigated by means of the following techniques: simultaneous thermogravimetry-differential thermal analysis, which allowed us to verify the thermal decomposition associated with endothermic or exothermic phenomena; and differential scanning calorimetry that was used to determine gelatinization enthalpy as well as the rapid viscoamylographic analysis that provided the pasting temperature and viscosity. By means of non-contact-atomic force microscopy method and X-ray powder patterns diffractometry, it was possible to observe the surface morphology, topography of starch granules, and alterations in the granules' crystallinity. © 2012 Akadémiai Kiadó, Budapest, Hungary.
Keywords: Cassava starch; Enthalpy; Gelatinization; Oxidized starch; Thermal analysis; Chemically modified; Modified starches; Pasting temperature; Sodium hypochlorite solution; Structural behaviors; Atomic force microscopy; Decomposition; Differential scanning calorimetry; Differential thermal analysis; Gelation; Granulation; Hydrometallurgy; Plants (botany); Thermoanalysis; Thermogravimetric analysis; Starch